Measurement of Z0-boson production at large rapidities in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (Physics letters, 2018)
The production of Z0 bosons at large rapidities in Pb-Pb collisions at sNN=5.02TeV is reported. Z0 candidates are reconstructed in the dimuon decay channel (Z0→μ+μ−), based on muons selected with pseudo-rapidity −4.0<η<−2.5 and pT>20GeV/c. The invariant yield and the nuclear modification factor, RAA, are presented as a function of rapidity and collision centrality. The value of RAA for the 0-20% central Pb-Pb collisions is 0.67±0.11(stat.)±0.03(syst.)±0.06(corr. syst.), exhibiting a deviation of 2.6σ from unity. The results are well-described by calculations that include nuclear modifications of the parton distribution functions, while the predictions using vacuum PDFs deviate from data by 2.3σ in the 0-90% centrality class and by 3σ in the 0-20% central collisions.